PENGEMBANGAN GAME RHYTHM: DHOL BEAT MENGGUNAKAN ALGORITMA RULE-BASED PADA ANAK-ANAK DI SANGGAR SENI ERFAM - Natalio, Jandri; Purwandari, Endina Putri; Renaningtias, Nurul (Jurnal Pseudocode, 2025)
Dhol is a traditional musical instrument of the Malay Bengkulu used in the Tabut ritual. The learning process for the Dhol musical instrument also takes place at Sanggar Seni Erfam. However, this learning process is not routine. Therefore, a reminder is needed so that they can repeat the beats they have learned at the sanggar. A rhythm game is a type of video game that emphasizes coordination of movements with rhythm or music, making it easier for children to recall the beats they have learned at the sanggar. A Rule-Based algorithm provides clear structure and control in gameplay development. The rule-based algorithm ensures that players start at a low level first, allowing them to understand the basic beats before moving on to more complex ones. With System Usability Scale testing to measure the effectiveness of the rule-based algorithm in the Dhol Beat Rhythm Game, a score of 81.12 was obtained, indicating that it is acceptable or has a good level of usability and can be concluded to be useful. Keywords : Dhol, Rhythm Game, Rule-Based Algorithm, System Usability Scale.